Feasibility of treating chlorinated solvents stored in low permeability zones in sandy aquifers - Bolhari, Azadeh, author; Sale, Thomas C., advisor; Bau, Domenico A., committee member; Shackelford, Charles D., committee member; Borch, Thomas, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: dilute plumes; remediation; low permeability zones; groundwater